THE EFFECTIVENESS OF ORAL HEALTH PROMOTION PROJECT IN A PRIMARY SCHOOL, YALA PROVINCE, THAILAND - Sarae, Rozikeen; Mudor, Adhiyah; Lappanakokiat, Napas (PEOPLE: International Journal of Social Sciences, 2017)
Globally, dental caries has been one of the most prevalent diseases and more common of children living in rural areas. Good oral health practices were started the early age lead to healthy teeth and gums later in life. Promotion and prevention are the most important processes in improving the students’ oral health, which will result in decreasing occurance of dental caries.Objective: The general aim of this study was to evaluate the effectiveness an oral health promotion project among 1st-grade students in a primary school. The specific objectives were to assess 1) 1st-grade students’ attitudes towards oral health. 2) oral health knowledge of their parents and teachers in a primary school, Yala province.Study Design: A cross-sectional descriptive study proceeded in a primary school, Yala province. The sample included 132 1st-grade students, 32 parents, and 6 teachers in the school. The instruments used in this study were 1) questionnaire about oral health self-care attitudes for students and 2) questionnaire about oral health care knowledge for parents and teachers. The descriptive statistic used in this study were percentage, mean, standard deviation and paired samples t-test was used to compare oral health knowledge of the parents and teachers, before and after they attended the project.Result: The result in this study shows mean score oral health attitudes among 1st-grade students was fairly high (M= 2.54 S.D.=0.38). There were no statistically significant differences in oral health knowledge of the parents and teachers, previously and afterward they attended the project.Conclusion: To have better oral health, every aspect including knowledge, attitude and practice should be improved altogether. The oral health promotion by interventions should be done, especially in parents who are responsible in taking care of children.